Proceedings of 35th International Cosmic Ray Conference — PoS(ICRC2017) 2017
DOI: 10.22323/1.301.1098
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high energy cosmic ray detector TUS: preliminary results of the first year of measurements

Abstract: For the Lomonosov-UHECR/TLE CollaborationTUS (Tracking Ultraviolet Set-up) is the first orbital detector of extreme energy cosmic rays. It was launched into orbit on April 28, 2016, as a part of the scientific payload of the Lomonosov satellite. The main aim of the mission is to test the technique of measuring UV fluorescent and Cherenkov radiation of extensive air showers (EAS) generated by primary cosmic rays with energies above 50 EeV. The first year of operation has revealed an unexpectedly rich diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To generate a reference data base (RDB) with 1000 simulated events, we choose the following parameters distribution: 2 The pixel distribution of the signal was performed using a 2D isotropic Gaussian PSF. The characteristic size of the PSF was selected to correspond to the control optical tests [12]. Measurements showed that the diameter of the circle of confusion with 70% of full energy of the image d 70 varies from 15 mm in the center of the photodetector to 23-27 mm at the edge.…”
Section: Simulated Events Reconstructionmentioning
confidence: 99%
“…To generate a reference data base (RDB) with 1000 simulated events, we choose the following parameters distribution: 2 The pixel distribution of the signal was performed using a 2D isotropic Gaussian PSF. The characteristic size of the PSF was selected to correspond to the control optical tests [12]. Measurements showed that the diameter of the circle of confusion with 70% of full energy of the image d 70 varies from 15 mm in the center of the photodetector to 23-27 mm at the edge.…”
Section: Simulated Events Reconstructionmentioning
confidence: 99%
“…An EAS can be detected as a track in the atmosphere with its ultraviolet (UV) radiation in the near-visible wavelength band of 300-400 nm. The TUS electronic trigger was designed to select UHECR transient tracks [5] and the first candidates for UHECR events were found and analyzed [6,7].…”
Section: Introductionmentioning
confidence: 99%